2023
DOI: 10.3389/fnagi.2022.1037816
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vortioxetine in patients with major depressive disorder and comorbid Alzheimer’s disease in routine clinical practice: An analysis of a post-marketing surveillance study in South Korea

Abstract: BackgroundVortioxetine has demonstrated procognitive effects in patients with major depressive disorder (MDD). We assessed the effectiveness and safety of vortioxetine in a cohort of patients with MDD and comorbid Alzheimer’s disease participating in a large post-marketing surveillance study in South Korea.MethodsSubgroup analysis of a 6-month, prospective, multicenter, non-interventional cohort study in outpatients with MDD with a pre-baseline diagnosis of Alzheimer’s disease receiving vortioxetine in routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…A newer SSRI, vortioxetine, has a broad range of effects on depressive symptoms, including cognitive symptoms [ 35 , 36 ]. An observational study by Cumbo E. et al [ 37 ] reported improvement in depressive symptoms in those with mild AD [ 37 , 38 ]. However, an RCT reported no superiority of vortioxetine over a placebo in improving depression [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A newer SSRI, vortioxetine, has a broad range of effects on depressive symptoms, including cognitive symptoms [ 35 , 36 ]. An observational study by Cumbo E. et al [ 37 ] reported improvement in depressive symptoms in those with mild AD [ 37 , 38 ]. However, an RCT reported no superiority of vortioxetine over a placebo in improving depression [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…These articles report encouraging results in the treatment of negative, cognitive and affective symptoms of schizophrenia [108][109][110], along with preliminary effectiveness in bipolar depression [111], burning mouth syndrome [112], postmenopausal depression [113], and panic disorder [114]. A further group of studies (n = 5) demonstrated that vortioxetine treatment is associated with affective and cognitive symptoms amelioration in patients with neurological conditions, including neurocognitive decline [115][116][117], Parkinson's disease [118], and post-stroke depression [119]. Interestingly, three studies report data suggesting that vortioxetine could be an effective strategy to reduce SSRI-induced emotional blunting [120][121][122].…”
Section: Analytical Observational Studiesmentioning
confidence: 98%
“…Działania niepożądane zgłosiło 27 pacjentów (13,0%) i były one w większości łagodne (89,2%). Po 24 tygodniach leczenia wortioksetyną u 71,4% pacjentów nastąpiła ogólna poprawa kliniczna, 51,9% osiągnęło remisję objawów depresyjnych [34]. Zestawienie wyników dotyczących skuteczności wortioksetyny przedstawiono na rycinach 1 i 2.…”
Section: Skuteczność W Znoszeniu Objawów Depresyjnych W Tym Zaburzeń ...unclassified
“…Wyniki globalnej poprawy klinicznej (CGII) u pacjentów z ciężkimi zaburzeniami depresyjnymi i współistniejącą chorobą Alzheimera po 8 i 24 tygodniach leczenia wortioksetyną (zestawienie analizy skuteczności). Bardzo duża poprawa: CGII = 1, znaczna poprawa: CGII = 2, minimalna poprawa: CGII = 3, bez zmian: CGII = 4, pogorszenie: CGII ≥ 5 [34] bardzo duża poprawa znaczna poprawa minimalna poprawa brak poprawy pogorszenie A B [36]. Pacjenci odnotowali również znaczną poprawę w zakresie codziennego i ogólnego funkcjonowania, zadowolenia z życia oraz jakości życia (HRQoL, BASQID) [37].…”
Section: Skuteczność W Znoszeniu Objawów Depresyjnych W Tym Zaburzeń ...unclassified
See 1 more Smart Citation